Police station meaning, closure and (in)visibility - Millie, Andrew (Policing and society, 2024)
This article considers the visual symbolism of policing as reflected by the presence or absence of police stations. The focus is England where recent years have witnessed a prolonged period of police station closure. The article draws on interviews with police estate managers and considers their reasons given for closure and consequent impact on visibility. The discussion is influenced by visual criminology and semiotics, as well as the concept of the abstract police developed by Jan Terpstra and colleagues, that police officers are now more abstract from the communities they serve, and from each other. Station closure was explained as being due to austerity, but also the unsuitability of ‘legacy’ buildings, changes in demand, and changes in police models. In these contexts, some closures may seem appropriate with public engagement maintained online. Moreover, poor community relations mean some may prefer not to have a local station. Yet, we argue that the visual presence or absence of a local police station can be read semiotically as a symbol of the police’s investment, or conversely lack of interest, in the community. The significance of these debates is discussed.